1998
DOI: 10.7863/jum.1998.17.12.765
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and nature of structural anomalies in fetuses with single umbilical arteries.

Abstract: Published studies differ concerning the rate of anomalies occurring in the presence of a single umbilical artery and the significance of the single umbilical artery as an isolated sonographic finding. We assessed the frequency, nature, and sonographic detection of structural anomalies in fetuses with a single umbilical artery. We identified all cases in which prenatal sonography diagnosed a single umbilical artery. Cases were excluded if postnatal physical or pathologic examination demonstrated a three‐vessel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 8 publications
(10 reference statements)
8
64
1
5
Order By: Relevance
“…Copel et al (20) advocate that sensitivity of four-chamber view is higher, whereas other authors consider this approach as low sensitive (4-40%) (14)(15)(16)(17)(18)(19)(20)(21). Usually FE studies report that fourchamber view has low sensitivity, obstetric ultrasound studies report high sensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…Copel et al (20) advocate that sensitivity of four-chamber view is higher, whereas other authors consider this approach as low sensitive (4-40%) (14)(15)(16)(17)(18)(19)(20)(21). Usually FE studies report that fourchamber view has low sensitivity, obstetric ultrasound studies report high sensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…Associated malformations (Table 1) are observed in 7.4-46% of fetuses with SUA 7. Chow et al found that 31% of fetuses with SUA also had other structural anomalies 8 . In a meta-analysis of 37 studies related to SUA, the mean incidence of congenital structural anomalies was 27% in live newborns, but increased to 66.3% in specimens obtained from early abortions, fetal deaths and autopsies 9 .…”
Section: Single Umbilical Arterymentioning
confidence: 99%
“…Some studies have also indicated that risks of some adverse pregnancy outcomes such as intrauterine growth restriction, low birth weight, preterm delivery, and hypertensive disorders in pregnancy could be increased in cases with a single umbilical artery (3,4). A single umbilical artery is known to be associated with fetal chromosomal and structural abnormalities particularly neural tube, musculoskeletal, genitourinary, and cardiac anomalies (5,6). The prognoses of fetuses with a single umbilical artery largely depend on the severity of the coexisting anomaly.…”
Section: Introductionmentioning
confidence: 99%